Designing Reading Materials For ESP Students Vocational High School Of Medical Science - Fauzi, Imam; Hanifah, Dian (Universitas Malikussaleh, 2019)
The study attempted to design reading materials for Medical Science students at one of Vocational High Schools in Serang. To produce satisfactory teaching materials, the researchers conducted the following steps: doing needs analysis, reviewing the principles of materials design and reading in a foreign language, designing course framework, syllabus, the reading materials, and implementing the sample lessons. Researchers employed qualitative methods in gathering the data. The instruments used were questionnaire and interview. The questionnaire was addressed to students, alumni, teachers and institution. The interview was collected from the users. The needs analysis was carried out by distributing questionnaires. The result of needs analysis, became the basis for the researchers to design course framework. The course framework was then developed into a syllabus. Finally the syllabus became the basis for designing reading materials. Reading materials for Vocational High School applied a topical syllabus. Each lesson or unit discusses different topics, greeting and introduction. Introduction about nurse, health, dialogue between nurse and patient, eat healthy food, profile a nurse, tools, disease, nutrition, the healthy diet pyramid. Each lesson also adopted various reading skills or strategies. They were skimming, scanning, and guessing meaning from context. When the materials had been designed, the researchers implemented six out of ten lessons of the coursebook. The results were satisfactory. Most students mentioned that the coursebook was related to their field of study. The majority of the students said that the materials were understandable and interesting. They also said that they were satisfied with the reading materials